Predicting Deviant Behaviors in Sports Using the Extended Theory of Planned Behavior - Kang, Sangwook; Kim, Inwoo; Lee, Keunchul (Frontiers in Psychology, 2021)
The purpose of the present study is to examine the deviant behaviors of young athletes the using extended theory of planned behavior (TPB) and impulsivity. About 536 middle and high school athletes in South Korea answered a set of questionnaires that measured their attitude, subjective norms, perceived behavioral control, intention, ethical obligation, and impulsivity. Structural equation model (SEM) analysis revealed that the extended TPB model is adequate to explain deviant behaviors in sports. Further, the underlying intentions that motivate the deviant behaviors of athletes in sports were significantly predicted by perceived behavioral control and moral obligation. Findings also suggested that the intention for deviant behaviors in sports more readily manifests as an actual act when the impulsivity scores are high. Theoretical contributions and practical implications are addressed in the Discussion section.